Sicily : land of love & strife - Spano, Mark, 1949- (Marcusceccu Investors LLC : Mark Spano Communications, 2018)
This exploration of Sicily takes the viewer to a place of spectacular beauty, epic human struggle, depth and diversity of culture, philosophic insights, and historic sites.